Question
Daniel expanded the expression as shown. What errors did he make? Select three options.
[tex]-2(-8x-4y+3/4)=-10x-8y-1 \frac{1}{4}[/tex]
A. The first term should be positive.
B. The second term should be positive.
C. The last term should be -1 1/2, not -1 1/4.
D. He divided -8 by -2 instead of multiplying -8 by -2.
E. He did not simplify the expression completely.
Answer:
Daniel's errors are (a), (b) and (c)
Step-by-step explanation:
To do this, we only need to solve the expression on the left.
So, we have:
[tex]-2(-8x-4y+3/4)=[/tex]
Open bracket
[tex]-2(-8x-4y+3/4)=-2 * -8x -2 * -4y - 2 * 3/4[/tex]
[tex]-2(-8x-4y+3/4)=16x + 8y - \frac{2 * 3}{4}[/tex]
[tex]-2(-8x-4y+3/4)=16x + 8y - \frac{6}{4}[/tex]
[tex]-2(-8x-4y+3/4)=16x + 8y - 1\frac{1}{2}[/tex]
From the expression, we can see that:
So, Daniel's errors are (a), (b) and (c)